The Relationship Of Hygine Sanitation, Sanitation Facilities and Exchanger Actions With Fly Density Levels in Dining House in Meulaboh City - Ihsan Murdani; Zakiyuddin Zakiyuddin; Jun Musnadi; Muhammad Iqbal Fahlevi; Maiza Duana (Journal of Nutrition Science, 2020)
It is known that the number of restaurants in the city of Meulaboh there are 66 restaurants. After observing the eating houses in the town of Meulaboh, can be in the know that sanitation eat less qualified home health such as ownership of the means of waste disposal, garbage disposal facilities, hand-washing facilities, washing facilities appliance. The purpose of this study is the relationship Sanitati:ion Hygiene, sanitation facilities, and action handlers Density With Flies On Eating In the city of Meulaboh. This research is an analytic method with cross sectional design. This research was conducted in the city of Meulaboh implemented Johan Pahlawan sub-district of West Aceh on 7 November to 5 December 2016, with a population of 66 homeowners and their eating of food handlers, the sampling technique is used total sampling method and analyzed by univariate and bivariate using chi-test square.The results showed that there is significant correlation between sanitation hygiene factors (P.Value = 0.006 <α = 0.05), sanitary facilities (P.Value = 0.025 <α = 0.05), action handlers (P.Value = 0.026 <α = 0.05 ) with the density of flies in the restaurant in the city of Meulaboh. It was concluded that there is significant correlation between the factors of hygiene sanitation, sanitation facilities, action handlers with the density of flies in the restaurant in the city of Meulaboh. with the density of flies in the restaurant in the city of Meulaboh to achieve a state of healthy foods that are not exposed to flies and protected from various diseases caused by flies.